2017
DOI: 10.1021/acs.inorgchem.6b02876
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Study of Unsymmetrical β-Diketiminato Copper(I) Complexes: Effect of the Chelating Ring

Abstract: β-Diketiminato copper(I) complexes play important roles in bioinspired catalytic chemistry and in applications to the materials industry. However, it has been observed that these complexes are very susceptible to disproportionation. Coordinating solvents or Lewis bases are typically used to prevent disproportionation and to block the coordination sites of the copper(I) center from further decomposition. Here, we incorporate this coordination protection directly into the molecule in order to increase the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 73 publications
2
32
0
Order By: Relevance
“…In general, the chelating pyridylmethyl arms form five‐membered rings with anionic β‐diketiminato moieties L1 – and L3 – , and the pyridylethyl arms form six‐membered rings with the anionic β‐diketiminato moieties L2 – and L4 – . In a chelating ring stability study of corresponding Zn II and Cu I complexes,, we found that the five‐membered chelating ring (pyridylmethyl arm) has a stronger tendency to become a pendent arm than the six‐membered chelating ring (pyridylethyl arm) in solution. Therefore, the unusual dinuclear structure formation of Li L3 may result from the hemilabile nature of the pyridylmethyl arm during the crystallization packing process.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In general, the chelating pyridylmethyl arms form five‐membered rings with anionic β‐diketiminato moieties L1 – and L3 – , and the pyridylethyl arms form six‐membered rings with the anionic β‐diketiminato moieties L2 – and L4 – . In a chelating ring stability study of corresponding Zn II and Cu I complexes,, we found that the five‐membered chelating ring (pyridylmethyl arm) has a stronger tendency to become a pendent arm than the six‐membered chelating ring (pyridylethyl arm) in solution. Therefore, the unusual dinuclear structure formation of Li L3 may result from the hemilabile nature of the pyridylmethyl arm during the crystallization packing process.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, our group reported the synthesis of UNAADpy ligands H L1 –H L4 using catalytic quantities of TsOH. The reaction was monitored for two days using 1 H NMR spectroscopy (Table ) , . We found that using one equivalent of TsOH gave low product yields that required further purification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cu-N py bond distances of complexes L 1 CuCl [2.0431( 18) Å] and L 3 CuCl [2.0308( 19) Å] are significantly longer than those of L 2 CuCl [2.020(4) Å] and L 4 CuCl [2.0080(2) Å] (Table 1); a similar behavior has been observed in copper(I) analogoues. 32 Therefore, the difference in the molecular structures of the copper(II) complexes L 1 CuCl-L 4 CuCl clearly suggests the disparities due to the length of the pyridyl arm supporting the β-diketiminato ligands. Apart from this, the Cu-N py bond distance of complexes L 1 CuCl-L 4 CuCl falls within the range of the reported data for the copper(II) complexes containing a pyridyl ligand.…”
Section: Papermentioning
confidence: 99%
“…19,27 However, lacking in the literature is a thorough study of copper complexes supported by unsymmetrical N-aryl-N′-alkyl-substituted β-diketiminato ligands in comparison with N,N′aryl-substituted analogues. 32 Based on previous studies of symmetric N-aryl-N′-aryl-substituted type of β-diketiminato copper (I) and copper(II) nitrite 19,28 and our work on biomimetic copper(I)-nitrito complexes, 29,30,33 we decided to introduce unsymmetrical N-aryl-N′-alkyl-substituted β-diketiminato ligands 32,34,35 into copper-nitrite chemistry. Herein, we describe the synthesis and structural characterization of unsymmetrical N,N′-aryl-substituted β-diketiminato L 1 CuCl-L 4 CuCl complexes (Scheme 2) and their nitrite complexes L 1 Cu(O 2 N) and L 2 Cu(O 2 N).…”
Section: Introductionmentioning
confidence: 99%